About Star Photometry on Digitized Astronegatives - Andruk, V.M.; Pakuliak, L.K.; Golovnia, V.V.; Shatokhina, S.V.; Yizhakevych, O.M.; Protsyuk, Yu.I.; Eglitis, I.; Eglite, M.; Kazantseva, L.V.; Relke, H.; Yuldoshev, Q.K.; Muminov, M.M. (Science and Innovation, 2024)
This paper discusses the issues of characteristic curve restoration for astronegatives exposed in the wide range of expositions in U, B Johnson color bands using different telescopes. Photographic plates are digitized by Epson commercial scanners. Digitized images are processed in MIDAS/ROMAFOT software. The accuracy of characteristic curve restoration using photoelectric data is in the range 0.1-0.2m.